Validity, Reliability and Feasibility of the Eating Behavior Pattern Questionnaire (EBPQ) among Iranian female students - Shabnam Salekzamani (Health Promotion Perspectives, 2015)
Background: The aim of this study was to assess the validity, reliability and feasibility of eating behavior pattern questionnaire (EBPQ) in female university students. Methods: In this study, after forward-backward translation, the questionnaire was reviewed by a panel of nutritionists and a psychologist and further thirty participants for the content validity measurement. The translated and modified questionnaire was completed by 225 female students of Tabriz University in 2013. Principle axis factoring, confirmatory factor analysis and known group analysis were conducted for construct, convergent and discriminant validity. Internal consistency and test–retest reliability were assessed by Cronbach’s α coefficient and intra-class correlation coefficient (ICC). Ceiling and floor effects were also performed for evaluating the feasibility of the instrument. Results: By using exploratory factor analysis, nine factors were extracted. Con-firmatory factor analysis confirmed the convergent validity. Cronbach ’s αand ICC were ranged between 0.55 to 0.78 and 0.67 to 0.89, respectively. The signif-icant difference for some three subscales between diabetes and healthy subjects determined the discriminant validity. No ceiling and floor effects were found. Conclusion: Our findings demonstrate the initial validity, reliability and feasibil-ity of the Iranian version of EBPQ as a useful tool for eating behavior studies in young females.